Evaluation of the playing time benefits of foreign players in the Big-5 European football leagues - Zhang, H.; Jiang, J. 1 (Journal of Human Kinetics, 2022)
To explore the benefits that foreign players bring to their clubs, this study used foreign players in the Big-5 European leagues (2013/2014-2017/2018 seasons) as samples and constructed a benefit model based on playing time and game points to evaluate the contribution of foreign players to their clubs in different leagues. The results showed the following: 1) from the 2013/2014 season to the 2017/2018 season, foreign players in the Bundesliga had the highest playing time benefits (PTBs) (0.526 ± 0.012), followed by foreign players in La Liga (0.523 ± 0.014), the Premier League (0.518 ± 0.011), Serie A (0.500 ± 0.012) and Ligue 1 (0.486 ± 0.011); 2) foreign players from South America had the highest PTBs in the Big-5 leagues, while those from Africa had the lowest PTBs. However, among the different leagues, there were no significant differences in the PTBs of foreign players from the same continent; 3) PTBs of foreign players in the forward position were lower than those of foreign players in the defender position; 4) the country that produced foreign players in the Big-5 leagues with the highest total PTBs was Brazil, followed by Argentina, Spain and France. Additionally, the top 15 countries by total PTBs qualified for either the 2014 or the 2018 World Cup Final.